A Mobile Application Architecture for Measuring Shaft Misalignment - Muhammad Suhaizan , Sulong; Mohd Shahir, Kasim; Azlianor Abdul , Aziz; Muhammad Hafidz Fazli, Md. Fauadi (2008)
Shaft alignment task is one of the important issues in manufacturing maintenance particularly to personnel who daily facing misalignment problem. The importance increase as shaft alignment needs high accuracy and precise measurement will reduces bearing and seal damage, minimizes energy loss, and reduces production downtime. Thus, in this paper we present an architecture in developing mobile application for shaft alignment that could saves the user the arduous task of using dial gauges. The aim is to solve engineering maintenance problem that runs on a Personal Digital Assistant (PDA) and brings the solution straight to the user’s fingertips. This would shorten processing time, provide reliable and better accuracy analysis and as a medium for data sharing thus increase communication level within a manufacturing plant.